2017
DOI: 10.1093/medlaw/fww046
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Patients from their Bad Decisions: Rebalancing Rights, Relationships, and Risk

Abstract: Patients have a right to autonomy that encompasses making medical decisions that others consider 'bad'. The ambits of this right in law and clinical practice are explored in this article, which describes an expansion of welfare protections across different aspects of medical law and explores their justifications and implications. In England and Wales, the Mental Capacity Act 2005 sets out protections for those who fall within its definition of incapacity. Those who retain capacity are ostensibly free to make d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Laws on involuntary psychiatric treatment focus on the presence of severe mental illness, need of treatment or danger to self or others but not on the patient's ability to make autonomous decisions (Sjöstrand et al, ). Certain critics of the implementation of AHDs in mental health uphold that users may cause themselves harm if their legal right to make a “bad decision” were honoured (Cave, ).…”
Section: Introductionmentioning
confidence: 99%
“…Laws on involuntary psychiatric treatment focus on the presence of severe mental illness, need of treatment or danger to self or others but not on the patient's ability to make autonomous decisions (Sjöstrand et al, ). Certain critics of the implementation of AHDs in mental health uphold that users may cause themselves harm if their legal right to make a “bad decision” were honoured (Cave, ).…”
Section: Introductionmentioning
confidence: 99%
“…One is to recognize that, in the specific context of information disclosure, the TE is necessary because the MCA does not adequately protect those who are unable to make an autonomous decision. This would continue a trend established in the recent development of the inherent jurisdiction to protect those who have capacity but lack the ability to make a voluntary decision (Cave, 2017). Conversely, this article has suggested that the MCA’s protective scheme extends to such patients, in which case a principled justification for the TE is lacking.…”
Section: Resultsmentioning
confidence: 99%
“…If so, this marks a divergent approach from the MCA 2005 which utilizes incapacity as the benchmark for best interests decision-making. Admittedly, such divergence is evident in recent developments of the inherent jurisdiction of the High Court to protect people from harmful involuntary decisions (Cave, 2017). 110 But the application of the inherent jurisdiction is judicial rather than clinical; it would be more difficult in the case of the TE to ensure that its application is facilitative of autonomy rights so as to enhance (rather than limit) commitment to Article 8 of the European Convention on Human Rights.…”
Section: Introduction: Montgomery V Lanarkshire Health Boardmentioning
confidence: 99%
“…The resolution of identity undertaken through engaging with treatment, working to reconcile a spoiled identity, is described by Camlin and colleagues (Camlin et al 2017) in Kenya and Uganda. Nobuhle's story extends the concept of therapeutic citizenship, showing how this may be threatened by refusing or delaying ART initiation, which she described being positioned as "breaking the law."…”
Section: Sifiso: Taking Time To Reconcile a Sense Of Self With Hivmentioning
confidence: 99%